Indigenous language translation using example-based approach / Neriza Nazar - Nazar, Neriza (2013)
Language has been a very crucial communication medium since the existence of human. Thousands of language created ever since. However, not all of them survive the human history. Language is a great asset to a culture and it represents the identity of a community. Yunani and Greek are some example of dead language. Of course there is available human translator however the number is decreasing day by day. In fear of Suluk becoming a dead language, this research is conducted. The aim is to create a translation application to preserve this indigenous language as well as a learning tool for beginner to learn Suluk language. This can be achieved by identifying methods that can be used in translating Malay to Suluk language, developing the prototype based on selected method and testing the prototype. After conducting the preliminary study, the approaches considered for this project is statistical approach, example-based approach and direct translation approach. To produce more reliable result, example-based approach is chosen considering both languages (Suluk and Malay) have different word order. In fact, deep linguistic understanding is not required thus making the example based approach the ideal method to be implemented. The end product of this project is a prototype that can be used to translate Malay to Suluk language. Translation is limited to direction commands only due to time constraint. This is a small step in helping the nation to preserve the heritage of our country.